2016
DOI: 10.1161/jaha.114.001234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Complexity on Health‐Related Quality of Life in Congenital Heart Disease Surgical Survivors

Abstract: BackgroundSurgical complexity and related morbidities may affect long‐term patient quality of life (QOL). Aristotle Basic Complexity (ABC) score and Risk Adjustment in Congenital Heart Surgery (RACHS‐1) category stratify the complexity of pediatric cardiac operations. The purpose of this study was to examine the relationship between surgical complexity and QOL and to investigate other demographic and clinical variables that might explain variation in QOL in pediatric cardiac surgical survivors.Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
(171 reference statements)
4
23
1
1
Order By: Relevance
“…Transposition of the Great Arteries and Ventricular Septal Defect correction normally requires only a single surgical intervention, whereas Tetralogy of Fallot often necessitates several surgical procedures and more hospitalisations. Interestingly, higher risk adjustment for congenital heart surgery categories was significantly associated with worse quality of life scores in paediatric cardiac patients, 30 which did not seem to be the case in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…Transposition of the Great Arteries and Ventricular Septal Defect correction normally requires only a single surgical intervention, whereas Tetralogy of Fallot often necessitates several surgical procedures and more hospitalisations. Interestingly, higher risk adjustment for congenital heart surgery categories was significantly associated with worse quality of life scores in paediatric cardiac patients, 30 which did not seem to be the case in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…These data are generally used to develop a model to predict or classify future events, or to find which variables are most relevant to the outcome. Examples of supervised learning algorithms include ordinary least squares regression,18 logistic regression,19 least absolute shrinkage and selection operator (LASSO) regression,20 ridge regression,21 elastic net regression,21 linear discriminant analysis,22 Naïve Bayes classifiers,9 support vector machines,23 Bayesian networks,24 a variety of decision trees25 especially Random Forests26 and AdaBoost or gradient boosting classifiers,27 artificial neural networks and ensemble methods 7. Some of the examples of supervised machine learning tasks include regression, classification, predictive modelling and survival analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our hypothesis and findings of other studies, healthrelated quality of life was comparable to children with biventricular forms of CHD. 2,5 Despite overall good health-related quality of life in children with mixed CHD at pre-school age, 6,11,12 children with singleventricle CHD seem to be at greatest risk for less favourable healthrelated quality of life. 2,[4][5][6] Goldberg et al reported on lower quality of life accompanied by poor functional status in single-ventricle CHD in comparison to healthy controls at 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Despite overall good health-related quality of life in children with mixed CHD at pre-school age, 6,11,12 children with singleventricle CHD seem to be at greatest risk for less favourable healthrelated quality of life. 2,[4][5][6] Goldberg et al reported on lower quality of life accompanied by poor functional status in single-ventricle CHD in comparison to healthy controls at 3 years of age. 9 An important difference to this particular study despite the comparison to healthy children, is the exclusion of children with genetic syndromes in our study, which are known to be at greatest risk for impaired quality of life and the comparison to healthy children.…”
Section: Discussionmentioning
confidence: 99%